1998
DOI: 10.1073/pnas.95.6.3042
|View full text |Cite
|
Sign up to set email alerts
|

Functional evidence for a nasopharyngeal carcinoma tumor suppressor gene that maps at chromosome 3p21.3

Abstract: Nasopharyngeal carcinoma is a malignancy that is prevalent among populations from Southeast Asia. Epidemiological studies indicate that genetic predisposition, Epstein-Barr virus, and environmental conditions may play a role in determining incidence. Molecular studies have implicated a tumor suppressor gene(s) on the short arm of chromosome 3. In this study we provide functional evidence, via monochromosome transfer, for a tumor suppressor gene(s) activity in chromosome 3p21.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(137 citation statements)
references
References 39 publications
6
130
1
Order By: Relevance
“…The presence of a functional tumor suppressor activity encompassing this region (Cheng et al, 1998) supports such a hypothesis. Homozygous deletions have been described in this region both in vitro and in vivo (Todd et al, 1997), but no mutations of any of the genes in this deleted region have been reported with high frequency in carcinomas in (Haber and Harlow, 1997;Sager, 1997).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The presence of a functional tumor suppressor activity encompassing this region (Cheng et al, 1998) supports such a hypothesis. Homozygous deletions have been described in this region both in vitro and in vivo (Todd et al, 1997), but no mutations of any of the genes in this deleted region have been reported with high frequency in carcinomas in (Haber and Harlow, 1997;Sager, 1997).…”
Section: Discussionmentioning
confidence: 63%
“…The telomeric breakpoint resides approximately 4 kb centromeric to the HYAL1 open reading frame, and overlaps with the centromeric region of the SCLC deletions. In addition to the chromosomal aberrations, the region encompassing 3p21.3 has functional tumor suppressor activity in vivo as determined by monochromosome mediated transfer in a nasopharyngeal carcinoma line (Cheng et al, 1998). Despite the frequency of homozygous deletions on 3p21.3 in various carcinomas, no mutations have been reported with high frequency in any of the candidate genes examined to date.…”
Section: Introductionmentioning
confidence: 99%
“…The exogenous chromosome 3 of MCH8.12, with a discrete deletion in the 3p24.2-3p22 region, and MCH12.10 containing an exogenous chromosome 3 harboring a significant deletion in 3pter-3p22 region were used. These cell line complementary DNAs were hybridized against their matched tumorigenic tumor segregants arising after selection in the mice (Cheng et al, 1998). Microarrays were scanned in a GenePix 4000A.…”
Section: Npc Tissue Specimensmentioning
confidence: 99%
“…NotI chromosome 3-specific microarray profiling is useful for screening for genes inactivated by deletion and/or hypermethylation. Comparative hybridization of tumorigenic NPC cell lines versus an immortalized nasopharyngeal (NP) epithelial cell line and also of previously established and characterized tumor-suppressive chromosome 3 microcell hybrids (MCHs) versus tumorigenic MCH tumor segregants (Cheng et al, 1998) can be used to identify chromosome 3 candidate tumor-suppressor gene (TSGs). A candidate gene, Fibulin-2 (FBLN2), which showed frequent methylation or deletion in NPC cell lines and tumor segregants, was thus, identified.…”
Section: Introductionmentioning
confidence: 99%
“…Microcells were prepared from the mouse A 9 microcell hybrid MCH903.1, which contain a normal human chromosome 3 with a neo selective marker (Cheng et al, 1998) and fused with the UOK 121 cells. Stable clones were selected using 600 mg/ml G418.…”
Section: Chromosome 3 Transfer Into Uok 121 Cellsmentioning
confidence: 99%